ASSOCIATION BETWEEN MATERNAL SERUM VITAMIN D AND EARLY PREGNANCY SPONTANEOUS ABORTION IN IRAQI WOMEN - Mohammed, Ashwaq Kadhim; Alqani, Vian Hussam Almansi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was aimed to estimate the Vitamin D serum concentration in a cohort of women with a history of recurrent spontaneous abortion. Methods: The current cross-sectional study was conducted at Al-Diwaniya maternity and child teaching hospital, Al-Diwaniya province, Iraq. Data collection, lab work, and procedures related to the study extended from August 2016 to August 2017. The study enrolled 42 women of childbearing age who have a history of spontaneous early pregnancy loss. From each woman, a venous sample was obtained and sent to a lab to assess serum Vitamin D concentrations using standard routine biochemical methods. Results: Assessment of mean maternal serum Vitamin D concentration revealed that the mean was 21.48Â±11.82 (ng/ml) and the range was from 5 to 50 (ng/ml). The number of women with low serum Vitamin D (<20 ng/ml) was 25 (approximately 60%), the results also revealed a highly negative correlation was obtained between number of abortions and maternal serum Vitamin D (r=âˆ’0.717, p<0.001) and that the value or R2 was 0.514 which indicated that the level of Vitamin D alone can act as an independent predictor to explain 51.4% of spontaneous abortions in the participating women. Conclusion: Vitamin D level is a strong predictor of pregnancy loss in early pregnancy, and that correction of Vitamin D status among Iraqi pregnant ladies may substantially reduce the frequency of spontaneous abortion.